La universalidad de la seguridad social y las trabajadoras no remuneradas del hogar. - Rosas Isa, Carlos Sebastián (2023)
The present research is entitled "The universality of social security and unpaid domestic workers”. The universality concludes that the rights belong equally to all people, whether they are men or women from the State, thus from here arises the importance of the appliance of this principle in the Ecuadorian social insurance. Consequently, the purpose of this investigation is to describe through a legal and doctrinal study, if the lack of affiliation to the social insurance of unpaid domestic workers, impinges on the labor rights violation. In order to accomplish with the objectives, this study was developed in three parts: the first one analyzes the appliance of the principle of universality with regard to social security and the mandatory affiliation to the IESS of all workers. The second part establishes whether the Ecuadorian legal regulations, which rules the social security and unpaid domestic workers, protects labor rights; the third part details the conceptualization of domestic work and the affiliation of these workers to social security in order to establish a conclusion according to the survey conducted. The methodological design is adapted to a social legal investigation through the inductive, analytical, descriptive and logical historical method, based on a qualitative research approach. It uses the types of basic research which are bibliographic-documentary, descriptive and field research; non-experimental research design. Additionally, information has been collected thanks to the research instruments, with which it has been possible to draw conclusions and recommendations according to the investigated problem.